Fixed nuclei as alternative template of BIOMED-2 multiplex polymerase chain reaction for immunoglobulin gene clonality testing in B-cell malignancies - Tang, Yuan (Am J Blood Res, 2015)
Evaluation of immunoglobulin (Ig) gene rearrangements with BIOMED-2 multiplex PCR has become a standard detection of clonality in mature B cell malignancies. Conventionally, this method is relatively labor-intensive and time-consuming, as it requires DNA isolation from bone marrow aspirates (BM) or peripheral blood (PB) in patients with BM or PB involvement. On the other hand, fluorescence in situ hybridization (FISH) is routinely used as genetic screening in B cell malignancies, but the surplus fixed nuclei initially prepared for FISH usually turn useless afterwards. We sought to use these surplus nuclei after FISH as a template to perform PCR-based Ig gene clonality testing. Templates of 12 patients with mature B cell malignancies, which consisted of both DNA isolated with commercial DNA isolation kit from fresh BM or PB (DNA group) and the fixed nuclei initially prepared for FISH (nuclei group) from the same individuals, were subjected to PCR with BIOMED-2 primer sets for immunoglobulin heavy chain and kappa light chain under recommended conditions. Our result, for the first time, showed a high consistency between the two groups in detecting B cell clonality, which indicates that nuclei for FISH can function as a reliable template comparable to fresh tissue-isolated DNA in PCR based Ig clonality testing. This offers a simple, rapid and more economical alternative to standard Ig testing based on regular DNA.